Modulação negativa do receptor metabotrópico de glutamato do tipo 5 como possível tratamento da obesidade induzida por dieta em camundongos C57BL/6J - Bruno Daniel Correia Gonçalves (2018)
Data from world health organization and Brazil health ministry shows a worldwide tendency for increased obesity and overweight prevalence. Obesity is a risk factor for several diseases including hypertension, diabetes, dyslipidemia, depression and others, due a series of physiological imbalances that can be stablished on obese individuals, such as a chronic inflammatory response for example. This inflammatory response derived from the adipose tissue is associated to the onset of insulin resistance, diabetes and cardiovascular problems. Obesity pharmacotherapy is based on drugs associated with several adverse effects and limitations regarding efficacy in promoting significant and sustained weight loss. All these factors highlight the importance of developing novel agents for obesity treatment. The metabotropic glutamate receptor 5 (mGluR5) is expressed in key areas that regulate metabolism, such as the hypothalamus, the mesolimbic reward system, the nucleus of the solitary tract and also at the periphery in leucocytes, hepatocytes and pancreatic cells. Previous works showed the therapeutic potential of this receptor in obesity. The present work used a negative allosteric modulator of mGLuR5, VU, never tested on obesity models. It was observed that obese C57BL6/J mice had elevated body weight, adiposity, serum leptin and cholesterol levels, and also developed an inflammatory response on white adipose tissue evidenced by higher levels of inflammatory cytokines. Treatment with 7,5 mg/Kg of VU promoted weight loss and decreased appetite only in obese mice. Furthermore, only obese mice treated with the compound had decreased serum insulin and inflammatory cytokines levels. It was also demonstrated that transgenic mice that do not express mGLuR5 (knockout) have reduced body weight and adiposity compared to their wild-type littermates. Collectively these results reinforce the role of mGluR5 receptors as potential therapeutic targets for treating obesity. It was also demonstrated the efficacy of VU to promote weight loss, reduce feeding and ameliorate the inflammatory response associated with the development of obesity, all risk factors for conditions such as insulin resistance, diabetes, metabolic syndrome and other pathologies. Further studies should clarify the mechanisms and pathways by which VU improved these parameters. Based on these results we conclude that VU, and possibly other negative allosteric modulators of mGluR5, could be important compounds for the treatment of obesity.